Examining the molecular basis of coat color in a nocturnal primate family (Lorisidae). Issue 9 (10th March 2021) - Munds, Rachel A.; Titus, Chelsea L.; Moreira, Lais A. A.; Eggert, Lori S.; Blomquist, Gregory E.
Abstract: Organisms use color for camouflage, sexual signaling, or as a warning sign of danger. Primates are one of the most vibrantly colored Orders of mammals. However, the genetics underlying their coat color are poorly known, limiting our ability to study molecular aspects of its evolution. The role of the melanocortin 1 receptor ( MC1R ) in color evolution has been implicated in studies on rocket pocket mice ( Chaetodipus intermediusi ), toucans (Ramphastidae), and many domesticated animals. From these studies, we know that changes in MC1R result in a yellow/red or a brown/black morphology. Here, we investigate the evolution of MC1R in Lorisidae, a monophyletic nocturnal primate family, with some genera displaying high contrast variation in color patterns and other genera being monochromatic. Even more unique, the Lorisidae family has the only venomous primate: the slow loris ( Nycticebus ). Research has suggested that the contrasting coat patterns of slow lorises are aposematic signals for their venom. If so, we predict the MC1R in slow lorises will be under positive selection. In our study, we found that Lorisidae MC1R is under purifying selection ( ω = 0.0912). In Lorisidae MC1R, there were a total of 75 variable nucleotides, 18 of which were nonsynonymous. Six of these nonsynonymous substitutions were found on the Perodicticus branch, which our reconstructions found to be the only member of Lorisidae that has predominantly lighter coat color; no substitutions were associated with Nycticebus . Our findings generate new insight into the genetics of pelage color and evolution among a unique group of nocturnal mammals and suggest putative underpinnings of monochromatic color evolution in the Perodicticus lineage. Abstract : In primates, the most colorful of mammals, few have examined the influence the melanocortin 1 receptor ( MC1R ) has on color variation (light or dark) in primates. Here, we examined how MC1R impacts color variation in a cryptic primate family with high contrasting color variation. We found MC1R is under purifying selection, but there appears to be a link in nucleotide changes and light coat color.